Curbing the lifestyle disease pandemic: making progress on an interdisciplinary research agenda for law and policy interventions - Brigit Toebes; Marlies Hesselman; Jitse P. van Dijk; Joost Herman (BMC, 2017)
Abstract By 2030, noncommunicable diseases (NCDs) will be the leading cause of death in every region in the world. While law and policy have an important role to play in curbing this pandemic, our current understanding of how they can most effectively be used is still limited. This contribution identifies a number of gaps in current research and insists on an interdisciplinary research agenda between law, health science and international relations aimed at designing concrete proposals for laws and policies to curb the NCD pandemic, both globally and domestically.